Effects of multiepisode case-based learning (CBL) on problem-solving ability and learning motivation of nursing students in an emergency care course - Gholami, Mohammad; Changaee, Farahnaz; Karami, Kimia; Shahsavaripour, Zahra; Veiskaramian, Atefeh; Birjandi, Mehdi (Journal of professional nursing, 2021)
Meeting the learning needs and developing the thinking skills of nursing students in caring for injured patients with complex, emergency, and unpredictable conditions is essential. The present study aimed to compare the effects of case-based learning (CBL) with multi-episode case studies and lecture-based learning (LBL) on the perceived problem-solving ability and learning motivation of undergraduate nursing students in an emergency care course. This study was conducted with a quasi-experimental, within-subjects, pretest-posttest design. Forty-three third-year undergraduate nursing students (as a single cohort) enrolled in the fall semester were selected using convenience sampling. The theoretical course of emergency nursing was taught to them using the LBL method (control group) during the first six weeks of the semester and then using the CBL method (intervention group) during the second six weeks of the semester through multi-episode cases in five steps. Outcomes including perceived problem-solving ability and learning motivation were measured using the Problem-Solving Inventory (PSI) and the Instructional Materials Motivation Scale (IMMS). There was a significant difference (P < 0.001) between the changes in the total mean score of perceived problem-solving ability and its subscales on the three measurement points, i.e. before lectures (pre-test), after lectures (mid-term test) and after CBL (final test). There was a significant difference between the LBL and CBL groups in terms of the students' total learning motivation score (t = 16.91, P = 0.000) and all its subscales after the CBL intervention. The study suggests that the CBL method applied through multi-episode cases is an effective approach to improving the perceived problem-solving ability and learning motivation of nursing students. •Multiepisode case -based learning effectively develops students' perceived problem solving skills, learning motivation and the preparedness to apply classroom content in emergency care.•Future studies are recommended to examine the effect of multiepisode case -based learning on other nursing students' cognitive outcomes.